STUDENTS’ PERCEPTION OF FEMALE LECTURER CHARACTERISTICS IN TEACHING: A STUDY OF THE IDEOLOGY OF GENDER SEGREGATION AT STATE UNIVERSITIES IN PONTIANAK - Andina Nurul Wahidah; Khairawati Khairawati (PSGA LP2M IAIN Pontianak, 2021)
This study seeks to examine students’ perceptions towards the characteristics of female lecturers at State Universities in the city of Pontianak and identify the position of the ideology of gender segregation in the realm of the lecturer as an occupation. This quantitative survey research employed a closed-ended questionnaire as the primary data collection instrument. The questionnaire was administered to 286 students of faculty of education at the state Universities in the city of Pontianak. Pearson product-moment was used to test the validity of the items in the questionnaire by taking those of r0.3 as the valid question items. The reliability test using SPSS Statistics version 23.0 showed the Cronbach alpha value of 0.75. Descriptive statistics as a data analysis method was carried out using SPSS Statistics version 23.0. The results of this study highlighted female lecturers’ characteristics and position in the ideology of gender segregation from the students’ point of view. First, students’ perception revealed (1) the characteristics of female lecturer namely sanguine personality type (33.98%), (2) the communication readiness dominated by the power factor (37.14%), and (3) personal-social characteristics at the negative extreme of easily offended (33.19%), at the central point of tolerance (14.13%), and at the positive extreme of attention (26.13%). Second, the lecturer, as an occupation in the public sector is suitable for women with a percentage of positive responses of 91.47% with the determinant factors for successful classroom teaching and learning comprising the quality cognitive, social, and personal characters of lecturers without gender segregation.